Detection of fluorescent powders and their effect on survival and recapture of Aedes aegypti (Diptera: Culicidae) - Rojas Araya, Diana (2019)
The use of insect markers, such as fluorescent powders, is a useful tool for studying ecological and epidemiological questions. Evaluating their effect on vectors of human disease agents, such as the invasive mosquito vector Aedes aegypti (Linnaeus), is crucial for their practical and reliable use, especially in parameters linked to the risk of disease transmission such as adult survival, dispersal, and host-seeking. Seven fluorescent powders (Hercules Radiant, DayGlo (DG), Risk Reactor (RR), and Angstrom Technologies), applied externally on cohorts of Ae. aegypti female mosquitoes, were tested to determine their impact on survival and recapture by baited mosquito traps, and their detectability after being exposed to controlled laboratory and semifield environments. There were no significant differences in survival among marked and unmarked females across all powders. Marked females were significantly less likely to be captured in baited traps relative to unmarked females, except for one of the DG powders. All females remained visibly marked on five parts of their body for 30 d (under both environments), except for one of the RR powders. The tested powders and application method are suitable for tracking mosquitoes throughout most of their lives under different environments, without significantly affecting their survival, but with potential impact on recapture by baited traps, possibly due to effects on senses or other physiological traits.